PENGARUH ORIENTASI PROFESIONAL TERHADAP KONFLIK PERAN DENGAN ANGGARAN SEBAGAI EVALUASI KINERJA DAN PARTISIPASI PENGANGGARAN SEBAGAI VARIABEL MODERATING - Asiah, Neng (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2011)
This research aims to analyze the effect of professional orientation toward role conflict and the effect of budget participation and orientation of system goal as moderating variables toward the relationship between professional orientation and role conflict. This research is performed by census method. The respondents are the physicians who hold a position as a Chief of Satuan Medik Fungsional (SMF) in public hospital of class A and B in Bekasi. The data analysis of hypothesis testing uses the Simple Regression Analysis and Moderated Regression Analysis (MRA). The results indicate that professional orientation influence role conflict positively. Budget use for performance evaluation goal are moderating variables which have positive effects toward the relationship between professional orientation and role conflict. Budget participation are moderating variables which have negative effects toward the relationship between professional orientation and role conflict.